Modelling and optimisation of the structural performance of lightweight polypropylene fibre-reinforced LECA concrete - Ja'e I.A.; Muda Z.C.; Amran M.; Syamsir A.; Amaechi C.V.; Al-Qadami E.H.H.; Huenchuan M.A.D.; Avudaiappan S. (Elsevier B.V., 2025)
Lightweight fibre-reinforced concrete integrates the advantages of lightweight aggregates with the strength-enhancing properties of fibres, resulting in a lighter composite with enhanced impact and mechanical performance. However, achieving an optimal balance between structural weight, and performance remains a challenging endeavour. This study investigates the mechanical properties, impact energy absorptions, flexural toughness, and crack resistance of lightweight fibre-reinforced concrete with the coarse aggregate entirely replaced with lightweight expanded clay aggregate (LECA). Concrete mixes containing 0 %, 0.5 %, 0.75 %, and 1.0 % Polypropylene fibre (PPF) and 10 % micro-silica were experimentally investigated. Predictions for concrete mixes with up to 2 % PPF were made using regression models developed from experimental data. The experimental and predicted results were analysed using response surface methodology. The findings reveal significant enhancements of up to 300 % and 570 % in toughness indices I5 and I10 at 1 % PPF, coupled with a 55.4 % increase in residual strength. Furthermore, an optimised slab thickness of 47 mm containing 1.73 % PPF yielded optimal impact energy absorption of 680 J and 2384 J and crack resistance of 3823 MPa and 16279 MPa at service and ultimate loading, respectively. These metrics represent improvements of 4.8, 15.2, 37, and 56 times, respectively, compared to the control samples. These substantial advancements highlight the potential of lightweight fibre-reinforced LECA concrete in engineering applications where balancing impact energy absorption, crack resistance, and structural weight is crucial. This innovative approach promises a transformative impact on the construction industry, paving the way for more efficient and resilient infrastructure. ? 2024